PENGARUH MODEL PEMBELAJARAN RADEC TERHADAP KEMAMPUAN BERPIKIR KREATIF PADA MATA PELAJARAN IPAS - Cindy Yunita Pratiwi; Sri Handayani; Jumanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study is to determine the effect of the RADEC learning model on creative thinking skills in IPAS subjects for fifth-grade students at SD N Tugu Jebres Surakarta in the 2024/2025 academic year. This research was conducted at SD Negeri Tugu Jebres Surakarta. The subjects of the study were all 27 fifth-grade students. The student population consists of 9 male students and 18 female students. This research is a pre-experimental study with a One Group Pretest-Posttest design. Data collection techniques were carried out through interviews, observation, documentation, and creative thinking ability tests. Data were analyzed using normality tests, homogeneity tests, and t-tests (Paired Sample T-Test) with the help of SPSS 25. The results of the analysis showed that there was a significant effect between the use of the RADEC learning model and students' creative thinking skills.Based on the results of the Paired Sample T-Test, a significance value of 0.000 < 0.05 was obtained, indicating a significant effect. Thus, the RADEC learning model is effective for improving students' creative thinking skills in IPAS subjects for fifth-grade elementary school